Evaluating a Moving Target: Lessons Learned from Using Practical Participatory Evaluation (P-PE) in Hospital Settings. (September 2013) - Wharton, Tracy; Alexander, Neil
This article describes lessons learned about implementing evaluations in hospital settings. In order to overcome the methodological dilemmas inherent in this environment, we used a practical participatory evaluation (P-PE) strategy to engage as many stakeholders as possible in the process of evaluating a clinical demonstration project. Demonstration projects, in this context, push the envelope about what is known about effectiveness in novel settings, and turnover of staff and patient populations can present challenges to gathering optimal data. By using P-PE, we built capacity in the environment while expanding possibilities for data collection. Suggestions are made based on our experience.